ANALISIS PENGARUH RETURN ON EQUITY, DEBT TO EQUITY RATIO, DAN CURRENT RATIO TERHADAP PRICE/EARNING RATIO (Studi pada Perusahaan Consumer Goods yang Terdaftar di Bursa Efek Indonesia Periode 2012-2015) - Sulistyawati, Poppy Dyah; Mahfudz, Mahfudz (Diponegoro Journal of Management, 2016)
Share  prices  on  stock  exchange  is  something  that  is  of  concern/signall  to  investor.  With  aPrice/Earning Ratio method, stock price reflected against of overall profit in listed companies. This research wants to examine the effects of Return on Equity, Debt to Equity Ratio (DER) and Current Ratio (CR) against Price/Earning Ratio of consumer goods company listed on the Indonesia Stock Exchange in the period 2012-2015.Data in this research used a sample of 24 consumer goods companies, with year observation period 2012 to 2015. The sample selection is done by purposive sampling method.The result of this research shows the result of regression analysis, found that partially Retun on Equity, have a positive significant to Price/Earning Ratio of Consumer Goods company. Current Ratio variable , have a negative significant to Price Earning Ratio of Consumer Goods company. While Debt to Equity Ratio doesn’t have influence to Price/Earning Ratio of Consumer Goods company. The three variable that used in this research Return on Equity (ROE), Debt to Equity Ratio (DER), dan Current Ratio (CR) simoultaneously have an influence to Price Earning Ratio of Consumer Goods company. The predictive capability of the three variable simoultaneously amounted 18,2%.